Cultural significance of termites in sub-Saharan Africa. Issue 1 (December 2017) - van Huis, Arnold
Abstract Background The number of termite species in the world is more than 2500, and Africa with more than 1000 species has the richest intercontinental diversity. The family Termitidae contains builders of great mounds up to 5 m high. Colonies are composed of casts: a queen, a king, soldiers and workers. Some species of termite cultivate specialised fungi to digest cellulose. Termites constitute 10% of all animal biomass in the tropics. The purpose of the study was to make an overview of how termites are utilized, perceived and experienced in daily life across sub-Saharan Africa. Method Ethno-entomological information on termites (Isoptera) in sub-Saharan Africa was collected by: (1) interviews with more than 300 people from about 120 ethnic groups from 27 countries in the region; (2) library studies in Africa, London, Paris and Leiden. Results Vernacular names relate to mounds, insects as food, the swarming, and the behaviour of termites. Swarming reproductive, soldiers and queens are collected as food. There are many different ways to harvest them. Termites can also be used as feed for poultry or as bait to catch birds and fish. The mushrooms that grow each year from the fungus gardens on the termite mounds are eaten. The soldiers, the fungus gardens and the soil of termite mounds are used for multiple medicinal purposes. Mounds and soil of termites have numerous functions: for geochemical prospecting, making bricks, plastering houses, making pots, and for storage. Termite soil is often used as fertilizer. The act of eating soil (geophagy) among women, especially those that are pregnant, is practised all over Africa. The mounds can serve as burying places and are often associated with the spiritual world, especially containing the spirits of ancestors. Termites also play a role as oracle, in superstitious beliefs, in art and literature. Conclusion The following characteristics make termites so appealing: the dominance in the landscape, the social organization, the destructive power, and the provision of food. The study shows that termites play a major role in peoples' lives, in physical as well as spiritual aspects.